MiR-181a-5p Delivered by Adipose-Derived Mesenchymal Stem Cell Exosomes Alleviates Klebsiella pneumonia Infection-Induced Lung Injury by Targeting STAT3 Signaling - Ren-Jing Hu; Xiao-Chun Chen; Lei Xu; Xiao-Hong Rui; Lin Wan; Jie Lu; Jun Liu; Hao Pei (Hindawi Limited, 2022)
Background. Klebsiella pneumoniae (K. pneu) is a leading cause of gram-negative pneumonia, which requires effective treatment. Adipose-derived mesenchymal stem cell- (ADSC-) derived exosomal microRNAs (miRNAs) have presented the inhibitory effect of multiple diseases. However, the function of ADSC-derived exosomal miRNAs in K. pneu remains unclear. Aim. In this study, we aimed to explore the effect of ADSC-derived exosomal miR-181-5p on K. pneu infection-induced lung injury. Methods. C57BL/6 mouse model was established by infection of K. pneu. ADSCs and exosomes were extracted and characterized in vitro. The translocation of ADSC-derived exosomes to bone marrow-derived macrophages (BMDMs) was detected. The level of miR-181a-5p was detected by real-time PCR. The secretion of inflammatory factors was determined by ELISA. The interaction between miR-181a-5p with STAT3 was identified. Results. We successfully isolated the ADSCs that express positive markers CD90 and CD105 rather than CD31 and CD45. The exosomal miR-181a-5p secreted by ADSCs were internalized by BMDM and K. pneu infection stimulated the miR-181a-5p level in bronchoalveolar lavage fluid (BALF) and BMDM. ADSC-derived exosomal miR-181a-5p repressed pulmonary outgrowth and dissemination of K. pneu infection in mice, repressed cellular infiltration in lung tissue, and attenuated the inflammasome activity and the levels of IL-1β and IL-18 in the lung. Mechanically, miR-181a-5p was able to inhibit STAT3 expression at posttranscriptional levels and repressed Nlrp3 and Asc expression in BMDM. Conclusion. Consequently, we concluded that ADSC-derived exosomal miR-181a-5p alleviated Klebsiella pneumonia infection-induced lung injury by targeting STAT3 signaling. ADSC-derived exosomal miR-181a-5p may serve as a potential candidate for the treatment of Klebsiella pneumonia infection-induced lung injury.